Aggregation-Induced Fluorescence of Carbazole and o-Carborane Based Organic Fluorophore - Jiao, Jiemin; Kang, Jia-Xin; Ma, Yanna; Zhao, Qianyi; Li, Huizhen; Zhang, Jie; Chen, Xuenian (Frontiers in Chemistry, 2019)
Carbazole based fluorophores 9-butyl-3,6-bis-(phenylethynyl)-9H-carbazole (1) and 9-butyl-3,6-bis-(2-phenyl-o-carborane)-9H-carbazole (2) were synthesized via Sonogashira type cross-coupling reaction and followed by insertion with decaborane. Compound 1 exhibited far more intense fluorescence than 2 in THF solution, while in solid state 2 exerted stronger fluorescence than 1. The fluorescence quenching behavior of 2 in THF solution could be attributed to the photo-induced electron transfer of donor-acceptor system in 2, which was confirmed by electrochemical experiments and DFT calculations. The fluorescence enhancement of 2 in solid state can be ascribed to aggregational induced packing which was evidenced by crystallographic study. In addition, compound 2 showed typical aggregation induced emission (AIE) behavior.